Factors influencing extent of nausea in the patients on oral iron therapy - Prokic, Andjelka M; Jankovic, Slobodan M (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Nausea after oral administration of iron is frequent phenomenon (11% of patients) and it is believed to be consequence of accumulation of free radicals in mucosa of gastrointestinal tract. The aim of our study was to measure the extent of nausea in outpatients taking oral supplementation with iron, and to investigate possible factors that may have an influence on it. Methods. The study was of the cross-sectional type, and conducted on a sample of outpatients on oral iron supplementation. The sample was consecutive, including all patients coming to a community pharmacy for oral iron supply during the study period. Frequency and severity of nausea were measured by the 5-item Drug-Induced Nausea Scale (DINS). Results. The mean score of the DINS from the sample of 128 patients was 8.56 ± 5.07 (range from 5 to 25). Each additional cup of coffee per week increased the DINS score for 0.143 points, the history of gastrointestinal disease had protective effect and decreased the DINS score for 5.923 points. Conclusion. Frequency and severity of oral iron-induced nausea are not dependent on oral iron burden, but rather on coffee intake and previous experience of patients with symptoms of gastrointestinal diseases. Modification of diet and education about types and severity of symptoms of gastrointestinal diseases could be useful preventive measures to avoid or at least mitigate oral iron-induced nausea and/or vomiting.
Keywords: iron; administration, oral; nausea; risk factors